Daddy-Long-Legs - Webster, Jean, 1876-1916. (Mineola, N.Y. : Dover, 2002)
Orphaned Judy Abbot relates her college adventures in letters to the mysterious benefactor that she calls Daddy-Long-Legs.
Includes bibliographical note
Originally published: 1912.
Keywords: Orphans -- Fiction; Letters -- Fiction; Universities and colleges -- Fiction